AAV2-mediated subretinal gene transfer of hIFN-α attenuates experimental autoimmune uveoretinitis in mice. - Lichun Tian (Public Library of Science (PLoS), 2011)
Background Recent reports show that gene therapy may provide a long-term, safe and effective intervention for human diseases. In this study, we investigated the effectiveness of adeno-associated virus 2 (AAV2) based human interferon-alpha (hIFN-α) gene therapy in experimental autoimmune uveoretinitis (EAU), a classic model for human uveitis. Methodology/principal findings An AAV2 vector harboring the hIFN-α gene (AAV2.hIFN-α) was subretinally injected into B10RIII mice at two doses (1.5×10(6) vg, 1.5×10(8) vg). AAV2 vector encoding green fluorescent protein (AAV2.GFP) was used as a control (5×10(8) vg). The expression of hIFN-α in homogenized eyes and serum was detected by ELISA three weeks after injection. The biodistribution of vector DNA in the injected eyes, contralateral eyes and distant organs was determined by PCR. EAU was induced by immunization with IRBP(161-180) three weeks following vector injections, and evaluated clinically and pathologically. IRBP-specific proliferation and IL-17 expression of lymphocytes from the spleen and lymph nodes were assayed to test the influence of the subretinal delivery of AAV2.hIFN-α on the systemic immune response. hIFN-α was effectively expressed in the eyes from three weeks to three months following subretinal injection of AAV2.hIFN-α vector. DNA of AAV2.GFP was observed only in the injected eyes, but not in the distant organs or contralateral eyes. Subretinal injection of both doses significantly attenuated EAU activity clinically and histologically. For the lower dose, there was no difference concerning lymphocyte proliferation and IL-17 production among the AAV2.hIFN-α, AAV2.GFP and PBS injected mice. However, the higher dose of AAV2.hIFN-α significantly suppressed lymphocyte proliferation and IL-17 production. Conclusions/significance Subretinal delivery of AAV2.hIFN-α lead to an effective expression within the eye for at least three months and significantly attenuated EAU activity. AAV2.hIFN-α was shown to inhibit the systemic IRBP-specific immune response.